UTILIZATION OF WASTE CANE (Saccharum officinarum) AS MIXED POLYURETHANE MATERIAL IN MAKING BUOY - Joza, Ahmad Riyanto; Syofyan, Irwandy; ', Isnaniah (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
This study was conducted in April 2015 in the material and fishing laboratory, Depatmane of agulatic resources wtilizatian. The aim fo the research is to giwe information abrut the lest composition of sugar cane dregs as a canpenal wite polyuretahane for buoy. The methad used is experimental suger cane dregt mixedinte polyurethane and descriptkehy analyzed. The results chaws that compointoin of compaud will raedi the bertresult if the ratius of polyurethane and suger cane dregt 3 : 1 (75 : 25 gr). Reaveage theyang is 151 gr at 100 %, meauwlile accordy to calculati pe bouyaucy 198373 m2.kgf, density 0,71 gr/m3, its volume 203,38 cm3 and Density value based reduction for 24 hours 923.25 kg/m3.Keywords: Cane Dregs (Saccharum officinarum). Bouy